Growth and yield of greenhouse eggplant under extended photoperiods using light emitting diodes - Terlizzese, Daniel; Lanoue, Jason; Little, Celeste; St. Louis, Sarah; Zheng, Youbin; Hao, Xiuming (Frontiers in Plant Science, 2026)
Supplemental lighting can significantly increase production of greenhouse vegetable crops during seasons of low natural light, but the cost of electricity to support supplemental lighting often poses a substantial burden on greenhouse growers. Electrical costs can be mitigated, while maintaining the same daily light integral (DLI), by decreasing the light intensity and extending the supplemental photoperiod. We provided greenhouse eggplant (Solanum melongena) cv. Jaylo with three distinctive supplemental light photoperiods: 16-hour of white light, 20-hour of white light, and 16-hour of white light followed by 8h of blue light [24-hour continuous lighting (CL)]. Each photoperiod treatment had a supplemental DLI of 8.64 mol day-1 and was compared to an unlit control group which only had natural light. No significant difference in fruit yield was found between any of the lit treatments, but supplemental lighting treatments increased total yield by 124-144% relative to the unlit control. A 20-hour photoperiod contributed to elevated levels of leaf stress early in the trial, recorded through dark-adapted and light-adapted chlorophyll fluorescence metrics, while plants treated with 16-hour of supplemental light achieved the greatest vegetative biomass. However, leaf stress was not recorded in the 20-hour treatment plants as the trial progressed, as the natural light DLI rose. Our data illustrated that a CL strategy resulted in similar yields and comparable plant growth as other supplemental photoperiods; therefore, we implore greenhouse eggplant growers to utilize a dynamic 24-hour photoperiod to possibly reduce the electrical cost of supplemental lighting during the winter.